“Pincéis como flechas”: UÝra em retomada transmídia - Corrêa, Marcos Paulo Souza (2024)
The formation of the Brazilian population was crossed by processes that involve a series of erasures of forms of culture, knowledge, languages and rituals. Specifically in relation to the indigenous presence, even though it has transformed and become mostly urban, there are at least four categories of indigenous peoples in Brazilian society: The isolated, those who remain living in communities, but have had contact with the population non-indigenous for more than 400 years, those who had more recent contact, and the urban indigenous population, which is the largest of all. For indigenous people who live in urban areas and are LGBTQIA+ there is another layer that must be taken into consideration in social life: we are the country that is at the top of the ranking of violence for environmental activists and for LGBTQIA+ people, with a life expectancy of 35 years for transgender bodies. In this context, Uýra, an indigenous and transgender visual artist, occupies a position as a target artist. This threatened body uses performance, associated with other languages, to carry out artistic and educational practices. In this research, we outline the artist's profile, investigate which languages are adopted within the scope of decoloniality in dialogue with the notions of media convergence and transmedia narrative. In order to understand and raise questions about the theme of resumption.